Comment on: “Macroseismic intensity assessment of 1885 Baramulla Earthquake of northwestern Kashmir Himalaya, using the Environmental Seismic Intensity scale (ESI 2007)” by Ahmad et al., 2013 - Shah, Afroz Ahmad (Pergamon-Elsevier Science Ltd, 2014)
This comment raises some scientific concerns regarding one of a recent publications in Quaternary International entitled “Macroseismic intensity assessment of 1885 Baramulla Earthquake of northwestern Kashmir Himalaya, using the Environmental Seismic Intensity scale (ESI 2007)” by Amad et al., 2013 (Article in Press). The authors have allegedly re-evaluated the historical reports of the 1885 Baramulla Earthquake of NW Kashmir by conducting extensive field investigations on those sites where environmental effects from the historical earthquake were reported. Thus, both primary (surface rupture) and secondary effects were studied and an ESI intensity of X was estimated for the epicentral area. However, the presented primary effects, on which the core of the contribution stands, are taken from Neve, 1928 and Jones, 1885 (cited in the prose) and provided secondary effects are not supported by any evidence(s). In my opinion the authors have not produced any new evidence to contradict or support the historical data.